Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) dalam Pembelajaran Koordinat Kartesius di Kelas VIII SMP Negeri 3 Motoling Timur - Hariyati Pantow; Anetha L.F. Tilaar; Vivian E. Regar (Journal on Education, 2023)
This study aims to determine the average difference in learning outcomes for Cartesian Coordinate material taught using the Numbered Headt Together (NHT) type cooperative learning model above the Minimum Completeness Criteria (KKM) score 0f 75. The population in this study was all students in class VIII of SMP Negeri 3 Motoling Timur consists of 2 classes with a total 60 students with a sample selected from 1 class, namely class VIII, totaling 30 students. The learning tools user are RPP and LKPD. The data obtained were the results of the Posttest of experimental class students with average 0f 88,26 and a standard devitation of 7,87. The data normaliry test is fulfilled, namely Lcount = 0,115 < Ltable = 2,045 where the data is normally distributed. The result of data analysis with a real level of 0,05 abtained tcount = 9,22 > ttable = 2,045 so that H0 was rejected and H1 was accepted. It was concluded that the average student learning outcomes in Cartesian Coordinate material taught using NHT type learning exceeded the Minimum Learning Completeness determined by the school namely 75.